Systematic Approach toward the Clinical Diagnosis of Functional Dyspepsia - Pierre Paré (Canadian Journal of Gastroenterology)
Functional dyspepsia (FD) is the most common condition in patients consulting with upper gastrointestinal tract symptoms, resulting in up to 5% of visits to family physicians. By definition, patients with FD have no clinical, biochemical or endoscopic evidence of an organic disease that is likely to explain their symptoms. The process to be used in a structured interview for establishing a clinical diagnosis of FD is presented. The steps are as follows: determine the duration and the course of the disease; characterize the current syndrome and review the alarm symptoms; elicit the patient-perceived dominant symptom and/or condition; and identify the patient’s reason for consulting and address the psychosocial factors. According to the clinical characteristics of the three most frequent causes of dyspepsia (peptic ulcer, gastroesophageal reflux and FD) and acknowledging that these conditions may coexist rather than overlap in some patients, an algorithm is suggested for establishing a working diagnosis of FD and indications for investigation, and initiating a management strategy.